Preclinical efficacy testing of three antivenoms against Naja ashei venom-induced lethality. (June 2022) - Okumu, Mitchel Otieno; Mbaria, James Mucunu; Gikunju, Joseph Kangangi; Mbuthia, Paul Gichohi; Madadi, Vincent Odongo; Ochola, Francis Okumu; Maloba, Kenneth Narotso; Nderitu, Joseph Gichuki
Abstract: This study aimed to determine the efficacy of Inoserp, Vins bioproducts, and South African Institute of Medical Research (SAIMR) polyvalent antivenoms in neutralizing Naja ashei venom-induced lethality in mice. The neutralization efficacy of the antivenoms were expressed as effective dose, median effective ratio, potency, normalized potency, volume, and the number of vials of antivenom required to neutralize 100 mg of Naja ashei venom (NAV). Graphical abstract: Image 1 Highlights: Naja ashei venom (NAV) has an i.p. LD50 of 3.02 (2.45–3.72) μg/g in mice. Vins bioproducts antivenom has poor efficacy against NAV-induced lethality. Inoserp and South African Institute of Medical Research polyvalent antivenoms have high potency in NAV-induced lethality.